Effectiveness of water filters used in the households of Dhaka city - Proma, Musharrat Shobnom; Oieshee, Monisha Hossain; Saifullah, Khaled; Tasnim, Jarin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.